Hypertrophic osteopathy and suspected subsequent disseminated intravascular coagulation in a dog with an abdominal gossypiboma. Issue 3 (19th May 2022) - Doyle, Eliana; Hall, Harriet; Hughes, Jonathan; Owen, Laura; Giuliano, Antonio
Abstract: An 8‐year‐old, female, neutered cocker spaniel presented with progressive lethargy, inappetence and right pelvic limb lameness. Regional mastectomy and ovariohysterectomy had been performed 11 months prior. Mild neutrophilia and increased C‐reactive protein were present. Radiographs revealed mild periosteal reaction of distal long bone diaphyses of all limbs, consistent with hypertrophic osteopathy. Abdominal imaging revealed a mesenteric mass with a central woven radiopaque foreign body diagnosed as a gossypiboma following surgical excision and histopathology. Postoperatively the patient developed acute decompensation of suspected chronic subclinical disseminated intravascular coagulation and suffered cardiac arrest. Hypertrophic osteopathy was confirmed with multifocal periosteal hyperostosis and concurrent myelofibrosis within the medulla of the long bones. Hypertrophic osteopathy occurs secondary to chronic inflammatory or neoplastic intrathoracic lesions and rarely due to abdominal pathology. To the authors' knowledge, this is the first description of hypertrophic osteopathy associated with an abdominal gossypiboma with sequential disseminated intravascular coagulation.